Perintisan Perpustakaan di Madin Salawiyah Desa Ngombak Kecamatan Kedungjati, Grobogan - Rasiman Rasiman; Umar Hafidz Asy'ari Hasbullah; Dwi Prasetyo Hadi; Adhy Purnomo (Universitas Islam Nahdlatul Ulama Jepara, 2020)
Madrasah Diniyah (Madin) as one of the non-formal educational institutions that is needed by the community at this time to provide provisions as the successor to the nation. So that the learning process in Madin runs well, various facilities are needed, including the availability of a library. The library is a place to find information sharing knowledge for students (santri). The availability of libraries in Madin Salawiyah, Ngombak Village, Kedungjati Sub-district, can help students form the habit of reading and seeking knowledge for students. Observation results show that: (1) open services are services that give students the opportunity to choose free books to read and take home, (2) closed services namely services that allow participants to visit the library at certain hours, and (3) students Madin Salawiyah showed high enthusiasm to visit the library. The results of dedication to library services can improve the optimization of services to students, scholars, clerics by applying the simplicity of service, responsibility, and convenience. In addition, good library services can have a good impact on library users, such as being able to motivate friends to actively read books, increase knowledge, make it easier to complete the tasks of the clerics and religious teachers. Therefore, the library Madin Salawiyah continues to evaluate the performance and quality of the library in order to create a conducive atmosphere for students in reading.